Learning and innovation skills in making contexts: a comprehensive analytical framework and coding scheme - Timotheou, Stella; Ioannou, Andri (My University, 2021)
With the Maker movement increasingly adopted across K‐12 schools and non-formal makerspaces, students are being given more opportunities to engage in Making activities using tools such as robots, electronics, arts, and crafts. Making activities are thought to help students develop twenty-first-century skills, especially communication and collaboration, creative thinking and problem solving, all of which come under the umbrella of learning and innovation (L&I) skills. The overall research question driving the study is: how do students develop L&I skills in Making contexts? To understand how students develop these skills we need frameworks and coding schemes which can help with skills’ identification and analysis. Finding such analytical tools with applicability in Making contexts has proven challenging. In Phase A, the present study proposes an analytical framework and coding scheme—the L&I skills in Making analytical framework and coding scheme—for the identification and analysis of L&I skills in Making contexts, informed by existing twenty-first-century skills frameworks as well as data from an empirical investigation with young learners. In Phase B, the applicability of the coding scheme is checked with a portion of the empirical data while evidence is presented for the identification and analysis of L&I skills in dialogic interactions during the Making activities. The study extends previous findings supporting that Making activities might be able to support students in developing twenty-first-century skills, but most importantly, has a unique contribution to the literature supporting researchers who are looking for an analytical framework and coding scheme to identify and analyse students’ L&I skills in Making contexts.
Keywords: Analytical framework; Coding scheme; Learning and innovation skills; Maker movement; Makerspaces; Making; STEAM; Twenty-first-century skills